Fenomena Gentrifikasi di Kawasan Strategis Kota Medan: Dampaknya Terhadap Hak atas Tanah Masyarakat Lokal dan Potensi Pelanggaran Hukum - Usy Zahra Ramadhani (Jurnal Hukum Lex Generalis, 2026)
Gentrification in Medan City's strategic areas encompassing the former Soewondo Air Force Base, ex-HGU land of PT KIM in Medan Deli and the coastal area of Medan Belawan threatens local community land rights. This study analyzes the gentrification process, its impact on land rights under Boedi Harsono's social function principle and resulting legal violations. Using an empirical juridical method with qualitative analysis, the study finds that gentrification is state-led, exacerbated by a regulatory vacuum following the revocation of the 2015 RDTR. Impacts include reduced land access, loss of legal certainty and inadequate compensation. Potential violations include illegal land occupation, non-procedural permitting and criminalization of communities defending their rights.